STUDENTS’ SPEAKING ANXIETY IN AN EFL CLASSROOM: GENDER PERSPECTIVE AT SMA NEGERI 2 KENDARI - Purwanti, Kiki; Jaya, Amir; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2019)
The aim of this study was to find out whether or not there was a significant difference of students’ speaking anxiety across gender. This study used survey method. The population was the second grade students of SMAN 2 Kendari in academic years 2017/2018. This study involved 184 students (92 males and 92 females) who were taken from proportionated stratified by random sampling. An instrument employed in this study was a questionnaire of Foreign Language   Classroom   Anxiety   Scale   (FLCAS).   The   data   were analyzed by using descriptive and inferential statistic. The result of descriptive analysis showed that students’ speaking anxiety was affected by three factors namely communication apprehension, test anxiety, and fear of negative evaluation where each factor had a neutral position and majority students had a moderately anxious level  on  speaking  anxiety.  The  result  of  the t-test  showed  that tobserved  was -2.007 and ttable  was 1.973. It means that ttable   was lower than the tobserved. Thus, there was a significant difference of speaking anxiety between male and female students where females were more anxious then male. Keywords:   Speaking   Anxiety,   situation-specific   Anxiety,   andGender.